AN ANALYSIS FIGURATIVE LANGUAGE IN THE SHORT STORY “Tale-Tell Heart” - Dewi Karimah; Lux Anggraeni; Nurina Rahmah Hayuningtias; Rahma Putri Yunia (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to analyze the types of figurative language contained in the short story "Tale-Tell Heart". This type of research is descriptive qualitative research. The source of the analyzed data comes from several sentences contained in the short story. The analysis technique used is content analysis. The data collected is in the form of words and sentences containing language style obtained through the identification of the short story text "The Tell-Tale Heart". The data was obtained using purposive technique based on the criteria of language style used. The researcher used qualitative research methods to analyze the data by observing the written text contained in the short story "The Tell-Tale Heart". The results showed that there are several figurative languages ​​in the short story "Tale-Tell Heart" by Edgar Allan Poe such as hyperbole, simile, personification and metaphor. Keywords : short story, figurative language, qualitative research